THE FIRST TEACHER IN KAZAKH STEPPE -IBIRAY ALTINSARİN - Ekrem AYAN (Fırat University, 2019)
Ibıray Altınsarin devoted his life to the education of Kazakh children, enlightenment of his people, protection of their rights and the most importantly, revival of Kazakh language. As most of his works are directed towards children, he is considered to be the father of Kazakh child literature. The effect of I. Altınsarin on the spiritual development of Kazakh Turks, who were entering into the revival and development period in late 19th century, was great. Foreseeing the serious outcomes of missionary works and Russification efforts, he penned the work entitled “Şartu’l Islam” to teach Islam religion to Kazakh people. In this work, he explained the main principles of Islam with verses of the Koran and Prophet Muhammad’s sayings. He worked as a teacher in a Russian-Kazakh school in 1860-1869 and during this period he invested great effort to open a school only for Kazakh children. So, some schools were opened and the teachers of the schools were selected and prepared by I. Altınsarin. He organized teacher training seminars. While he was thinking that there would be a need for new books to be published, he examined many books from Russian and Western literatures and he himself wrote some books. Moreover, he wrote a grammar and a religious book. In the written Kazakh Literature, the basis of child literature was laid by I. Altınsarin, he is the founder of child literature.